Risk Level Assessment of Pre-Organization of Football Events with Information Technology-Based Likelihood and Severity Analysis Approach - Toni Bagus Murdjayanto; Dewi Kurniasih; Priyambodo Nur Adi; Imam Sutrisno (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
One of the most popular sports events in Indonesia is football. In running high-tension football matches, safety and security factors are of utmost importance. There are many potential risks in a football match that could endanger the safety of spectators, players, officials, and event organizers, such as the risk of riots. This study aims to analyze the inherent risks affecting the pre-event stage of a football match at the Gelora Bung Tomo Stadium, Surabaya. Additionally, this research analyzes and determines the risk assessment at the pre-event stage in terms of human, environmental, operational, and financial aspects using Likelihood and Severity analysis. The outcome of this research is the development of a risk assessment information system by implementing Crowd Risk Mitigation Technologies (CRMT) to support more effective and predictive risk management. The data and information processing is based on variables and indicators that affect the potential occurrence of an event (likelihood) and the adverse impact if the event occurs (severity). Indicators are assigned weighted values according to the event scale, such as low, medium, and high risks, resulting in a Risk Matrix. The risk value results will be implemented in the Crowd Risk Mitigation Technologies (CRMT) application program, which serves as a tool to facilitate the initial mapping of the pre-event conditions for a football match. This study aims to analyze Inherent Risk at the pre-event stage of a football match at Gelora Bung Tomo Stadium. The analysis process uses likelihood and severity approaches to assess the probability and impact, resulting in a Risk Matrix. The findings show that human risk has the highest relative risk index (77.5%), related to potential conflicts and violations, environmental risks have a relative risk index of 16.3%, indicating risks of facility damage, and operational risks have a relative risk index of 6.4%, indicating dominant risks related to system failures and coordination issues. The potential financial loss reaches 1.53 billion Rupiah (very high level), with the largest contribution from human risks (888 million Rupiah), followed by operational (375 million Rupiah) and environmental risks (250 million Rupiah). With a structured and cross-data approach, the Crowd Risk Mitigation Technologies (CRMT) application is implemented as a tool for assessing pre-event football risks.